Cervical Cancer - Chatterjee,J (Oxford University Press, USA, 2015)
Evidence base Clinical trials in cervical cancer There are several ongoing clinical trials in cervical cancer: The surgical trials include study on sentinel nodes and various techniques for surgical staging. CIRCCa (Cediranib in Recurrent ...